PEMBERIAN RATIONAL-EMOTIVE BEHAVIOR THERAPY DAN ASSERTIVE TRAINING SEBAGAI UPAYA MENGURANGI PERILAKU AGRESIF PADA REMAJA DI PAUH PADANG - Rika Sarfika; Nelia Afriyeni; Hermalinda Hermalinda; Feri Fernandes Feri Fernandes (LPPM Universitas Andalas, 2020)
The aggressive behavior of adolescents in the Padang is very unsettling and even leads to criminal. The impact of this aggressive behavior can be detrimental to adolescents, their families and communities. The purpose this activity to reduce the aggressive behavior of adolescents through Rational Emotive-Behavior Therapy (REBT) and Assertive Training (AT). The participants of this activity consisted of teenagers from public senior high school 15 Padang and 9 Padang. A total of 36 students from these schools were formed into 2 therapeutic groups. Criteria for participants in this activity are students with aggressive behavior and declare willingness to follow the activity for two weeks. Before and after therapy, adolescents were given the Agression Questionaire (AQ) questionnaire to measure the aggressive behavior of adolescents. Data were analyzed using paired t-test. The results show that there were significant changes in the aggressive behavior of adolescents before and after REBT-AT. Significant changes were found in the physical aggression and hostility. However, in verbal aggression and anger there were no significant changes. Based on the results, REBT-AT has not reduced all components of adolescent aggressive behavior. Ideally, to get maximum results, therapy should be given for 4 weeks for REBT and 4 weeks for AT. Therefore, it needs further evaluation for 8 weeks to find out the results of the program to reduce aggressive behavior.